Fraud risk as perceived by external auditors: Evidence from Tunisia - Ayadi, Salma Damak; Ennar, Hager (The journal of contemporary issues in business and government, 2022)
Purpose - This study aims to explore the Tunisian external auditors’ perception of fraud risk, the process of fraud risk assessment and their responses to it. Design - Through a qualitative study, the analysis draws on a total of 20 semi-structured interviews conducted with auditors from Big 4 and Non-Big 4 audit firms. Findings - The results demonstrate the importance given to fraud risk and reveal some ambiguities encountered during the audit engagement regarding this risk. They also highlight the necessity of exercising professional judgment and skepticism. Research limitations - Even though audit planning involves the nature, extent, and timing of audit procedures, the present work did not take their efficiency into consideration. Practical implications - Highlighting ambiguities and raising concerns about auditors’ responsibilities regarding fraud risk may interest standard setters and audit firms as they both strive to improve the ability of auditors to identify fraud risk and to respond to it appropriately. Originality/value - Our investigation allows auditors to speak up about their concerns regarding fraud risk and their ability to address it. Interviews were used to deepen our knowledge about this issue within an emerging country, Tunisia.